The Mediating Role of Work Satisfaction in the Effect of Ethical Leadership on Employee Performance - Dino Manarso; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Through the utilisation of job satisfaction as a moderating factor for PT "X" Employess, this research endeavours to investigate and assess the ways in which ethical leadership influences worker performance. This particular study utilised a quantitative research design as its methodology. A total of 112 respondents, which represents the entire population, were included in the sample for the study. The technique for collecting data included the distribution of questionnaires to each individual who participated in the survey. The next step was to conduct testing in order to determine the direct and indirect effects that the research elements had. The findings of the study suggest that ethical leadership does not have a substantial impact on the degree to which employees accomplish their jobs. Taking into account the level of job satisfaction experienced by employees, it was shown that ethical leadership had an effect on performance in just 26.9% of instances. There was only a 26.9% correlation between ethical leadership and employee performance, which was measured by work satisfaction. The remaining percentage of employee performance was explained by criteria that were not included in the study. The findings of the study also indicate that ethical leadership may not directly influence employee performance at PT "X" on its own. It is instead the job satisfaction that emerges as a mediating variable, which helps to mitigate the impact that ethical leadership has on personnel.